2021
DOI: 10.1111/scs.12963
|View full text |Cite
|
Sign up to set email alerts
|

Newly graduated nurses’ evaluation of the received orientation and their perceptions of the clinical environment: An intervention study

Abstract: Background New graduate nurses (NGN) are the future of healthcare organizations where a shortage of nurses will soon be reality. The transition from a student to a registered nurse can be a demanding and challenging time, and in order to retain new graduate nurses, the transition should be as smooth as possible. AimThe aim of this study was to examine preceptors’ education intervention’s impact on NGNs’ orientation period and their clinical learning environment from NGNs’ point of view. Material and Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In this study, the lowest levels of feeling socially connected and lowest reported levels of all types of incivility occurred at this stage. This is consistent with the study of Lindfors et al (2022), who reported that prepandemic NGNs in orientation perceived their unit as welcoming and colleagues supportive of their learning. NGNs at this stage rated their self-confidence and feelings of transition to practice completion at a low level, consistent with Duchscher's (2008) description of NGNs' feelings during transition shock.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the lowest levels of feeling socially connected and lowest reported levels of all types of incivility occurred at this stage. This is consistent with the study of Lindfors et al (2022), who reported that prepandemic NGNs in orientation perceived their unit as welcoming and colleagues supportive of their learning. NGNs at this stage rated their self-confidence and feelings of transition to practice completion at a low level, consistent with Duchscher's (2008) description of NGNs' feelings during transition shock.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study by the American Nurses Association (2022), 66% of participants ( n = 11,964) reported experiencing incivility or violence from patients, families, the public, and other staff nurses. In prepandemic studies, a healthy work environment, a supportive preceptor, and ongoing feedback from the supervisor contributed to NGNs’ feelings of receiving a higher quality orientation (Lindfors et al, 2022). Work-based relationships characterized by incivility are perceived as stressful by NGNs who, because of their novice status, are dependent on experienced nurses for help (Urban & Barnes, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Protected orientation time is necessary, yet participant orientation in this study was said to be cut short as a response to exorbitant staffing shortages. Orientation should not be cut short, however, in practice this continues to occur, having significant implications on new graduate nurses – both decreasing their confidence as an independent practitioner and increasing their desire to leave the workplace ( Kiel, 2020 ; Lindfors et al, 2022 ; Schmidt & Schiffman, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Duchscher (2008) correlates transition shock to an inadequate time for adjustment. Optimally, orientations are individually structured with consideration for an NGN's personality, resilience, and clinical experience (Lindfors et al, 2022). With Emily's undergrad experiences in acute care, extending the orientation offered additional time to acclimate to the unfamiliar workplace routines, roles and responsibilities, and clinical practice expected of a rural home care nurse.…”
Section: Case Study Analysismentioning
confidence: 99%